HIGHER EDUCATION WITHIN ASEAN CONNECTIVITY - Yuliana Riana; Cornelia Alverina (Kajian Asia Pasifik, 2018)
ASEAN member countries are well aware of the importance of education to be one of the decisive factors in developing a high quality of human resources. This is reflected in the inclusion of education in ASEAN socio-cultural cooperation dimension. This review will highlight the implementation of higher education in ASEAN connectivity described in five steps. Infrastructure connectivity makes the mobility of young people in ASEAN members become easier in pursuing education across ASEAN region. In addition, the improvement of facilities and infrastructure in educational institutions could support a conducive atmosphere in the teaching and learning process. Institutional connectivity could also develop human resources who are not only knowledgeable but also have compatible skills with industry needs in ASEAN. In regional level, connectivity through ASEAN University Network will develop quality standards between AUN members which can be used as a benchmark standard of university quality in ASEAN. Young generation connectivity through students’ exchange program between many universities in ASEAN not only for knowledge exchange but also to understand each other’s cultural diversity. Connectivity is the success key in building the ASEAN community. Connectivity plays a role in helping to reduce education gaps among ASEAN member countries. Higher education within ASEAN connectivity will strengthen regional cooperation between university institutions and students in ASEAN, also will enhance the internationalization of competitive and high-quality education. Keywords: connectivity, ASEAN, education